AN ASSESSMENT OF ANTIBIOTICS-RELATED KNOWLEDGE LEVELS AND BEHAVIORS OF PATIENTS PRESENTING TO FAMILY PRACTICE CENTERS - (:unkn) unknown (My University, 2019)
INTRODUCTION: The aim of study is to evaluate the knowledgelevel and behaviors of the patients who applied to the family practicecenter on antibiotics.MATERIALS AND METHODS: This is a descriptive type study. In thestudy a questionnaire with 43 questions was applied face to face to 250individuals who admitted to the family practice centers evaluating thesocio-demographic characteristics and knowledge and behaviors aboutantibiotics. Data analysis was performed by using descriptive statisticalmethods (mean, standard deviation, frequency) and chi-square test inSPSS 22.0 program. p<0,05 was considered statistically significant.RESULTS: The mean age of the 250 participants was 39.23±14.86(min=15-max=82). Of participants, 62.8% (n=157) stated that theyhad an infection in the last year. Of participants, 58.8% (n= 147) usedantibiotics at least once. While 28.0% (n=70) had substitute antibioticsat home, 37.6% did not know the purpose of antibiotic use. The rateof non-prescription antibiotics use in the last one year was 10.0%(n=25). It was determined that young people used more antibioticswithout prescription (p<0.01). Men were less aware of the purposeof antibiotic use than women (p=0.001), and the low-level educatedgroup had more false information (p=0.011). The most importantsource of information on antibiotics was doctors 62.4% (n=156).Seniors were using television and the young adults were using theinternet more as source of information (p=0.08; p=0.02).CONCLUSION: It was determined that the participants did nothave sufficient knowledge level for rational antibiotic use and this wasreflected in their behaviors. The most important factor for rationalantibiotic use is physicians and there is a need for training programsthat will use appropriate communication methods according to ageand education level. Family physicians, who play an important role inraising the awareness of the society, should be more active in education.

AMAÇ: Çalışma, aile hekimliği polikliniğine başvuran hastaların antibiyotiklere dair bilgi düzeylerini ve davranışlarını değerlendirmek amacıyla yapılmıştır. GEREÇ VE YÖNTEM: Bu tanımlayıcı tipte bir çalışmadır. Araştırmada sosyo-demografik özellikleri, antibiyotik hakkında bilgi ve davranışları değerlendiren aile hekimliği merkezlerine başvuran 250 kişiye yüz yüze 43 sorudan oluşan bir anket uygulanmıştır. Veri analizleri SPSS 22.0 programında, tanımlayıcı istatistiksel yöntemler (ortalama, standart sapma, frekans) ve Ki-kare testi kullanılarak yapıldı. p<0,05 istatistiksel olarak anlamlı kabul edildi. BULGULAR: Çalışmaya katılan 250 kişinin yaş ortalaması 39,23±14,86 (min 15-maks 82) idi. Katılımcıların %62,8'i (n = 157) geçen yıl enfeksiyon geçirdiğini belirtmiştir. Katılımcıların %58,8'i (n = 147) en az bir kez antibiyotik kullanmıştır. %28,0'ı (n = 70) evde yedek antibiyotik bulundururken, %37,6'sı antibiyotik kullanımının amacını bilmiyordu. Son bir yılda reçetesiz antibiyotik kullanım oranı %10.0 idi (n = 25). Gençlerin daha fazla reçetesiz antibiyotik kullandığı tespit edildi (p<0,01). Antibiyotik kullanım amacını erkekler kadınlardan daha az biliyordu (p=0,001), eğitim seviyesi düşük grup daha fazla yanlış bilgi sahibiydi (p=0,011). En önemli bilgi kaynağı hekim %62,4’ı (n=156) olarak görülse de yaşlılar televizyonu, genç erişkinler interneti daha fazla bilgi kaynağı olarak kullanıyordu (p=0,08; p=0,02). SONUÇ: Çalışmaya katılan kişilerin akılcı antibiyotik kullanımı için yeterli bilgi düzeyine sahip olmadığı, bu durumun tutum ve davranışlarına yansıdığı belirlendi. Akılcı antibiyotik kullanımı için en önemli unsur hekimler olup yaşa ve eğitim düzeyine göre uygun iletişim yöntemleri kullanılacak eğitim programlarına ihtiyaç vardır. Toplumun bilinçlendirilmesinde önemli rolü olan aile hekimlerinin eğitimde daha aktif rol almaları uygun olacaktır.
AİLE HEKİMLİĞİ POLİKLİNİĞİNE BAŞVURAN HASTALARIN ANTİBİYOTİKLER İLE İLGİLİ BİLGİ DÜZEYİ VE DAVRANIŞLARININ DEĞERLENDİRİLMESİ